Increased biogas production from swine waste by using microbial additives - Li Ming Wai (1991)
This thesis deals with the investigation of the effect of physical and bacterial pretreatment on the batch digestion of swine waste for biogas production. The swine slurry shows a number of peaks in gas production rate occurring at different times during the digestion. The physical pretreatment of swine waste was done by blending the slurry having total solids (TTS). concentration of 23.94 g/liter. The results show a 16 to 23% increase in gas production and a shorter digestion period of 25 days compared to 40 days for non-blended slurry. The cumulative biogas yield was 17.445 ml with an average of 73% methane per kilo substrate into the digester.